Posterior reversible encephalopathy syndrome – A case report - Kostić, Dejan Ž; Brkić-Georgievski, Biljana; Jovanovski, Aleksandar; Kostić, Smiljana; Ivetić, Dražen; Sekulović, Leposava (Vojnosanitetski pregled, 2015)
Introduction. Posterior reversible encephalopathy syndrome (PRES) is characterized by the following symptoms: seizures, impaired consciousness and/or vision, vomiting, nausea, and focal neurological signs. Diagnostic imaging includes examination by magnetic resonance (MR) and computed tomography (CT), where brain edema is visualized bilaterally and symmetrically, predominantly posteriorly, parietally, and occipitally. Case report. We presented a 73-year-old patient with the years-long medical history of hipertension and renal insufficiency, who developed PRES with the symptomatology of the rear cranium. CT and MR verified changes in the white matter involving all lobes on both sides of the brain. After a two-week treatment (antihypertensive, hypolipemic and rehydration therapy) clinical improvement with no complications occurred, with complete resolution of changes in the white matter observed on CT and MR. Conclusion. PRES is a reversible syndrome in which the symptoms withdraw after several days to several weeks if early diagnosis is made and appropriate treatment started without delay.
Keywords: brain diseases; syndrome; diagnosis; treatment outcome